Medical Tourism and Wellness : Hospitality Bridging Healthcare (H2H). - DeMicco, Frederick J., ....- (Oakville/Waretown : Apple Academic Press, 2017)
Medical Tourism and Wellness: Hospitality Bridging Healthcare (H2H) takes a systems approach to examining the growing field of medical tourism, one of the field's hottest niches, with billions of dollars spent each year. This important book fills the need for a modern management book that looks at medical tourism in depth from a medical and hospitality operational management perspective. Growing numbers of people are going abroad to find affordable quality medical care for both necessary and cosmetic medical services. When they require surgery or dental work, they combine it with a trip to the Taj Mahal, a photo safari on the African veldt, or a stay at a luxury hotel-or at a hospital that feels like one-all at bargain-basement prices. The book takes a comprehensive look at medical tourism, covering such topics as: The history of medical tourism Why patients/tourists decide to travel for medical care The role of professional facilitators of medical tourism Key countries and medical disciplines in medical tourism Transportation, food, entertainment, and hotel/hospitality services Hotel and spa designs for medical tourism Best practices in medical tourism Patient follow-up after medical discharge Future trends in medical tourism Careers in medical tourism With the inclusion of case studies, the book provides a comprehensive look into this growing trend and will be valuable to upper-level undergraduate and graduate students in health care administration and those pursing MBAs in healthcare, medical students pursuing a management focus, and students in hospitality management. It will also be a must-have resource for professionals working in hotels and in health care.
Keywords: Medical Tourism; Toerisme -- Medisch toerisme